The impact of enlightenment on the emergence of atheism - NorAzali, Nor Irdina Hakimah; Mohd Nor, Nur Suriya (IIUM Press, 2023)
This research investigates the intricate relationship between the Enlightenment era and the emergence of atheism as a significant intellectual and philosophical movement. Fueled by an epistemology spirit of reason, empiricism, and skepticism, the Enlightenment era provided fertile ground for the development of atheistic thought, challenging prevailing religious authorities and fostering the advancement of secular perspectives. This research is significant in a way it scrutinizes the original form of atheism by analysing the worldview of some atheist figures in various field such as politics, economy, nature science and psychology. Taking cues from the various arguments that atheists put forward, this research addressed critical arguments to aid Muslims to confront many of the arguments raised by the atheists and hopefully enrich the awareness of Muslim response to atheism. This research employed qualitative methodology that incorporates the approach of collection data from the primary and secondary sources. The major approaches, namely descriptive and critical analysis are implemented throughout the study to analyse data.